Striving for better health in South-East Asia - Rafei, Uton Muchtar; World Health Organization. Regional Office for South-East Asia. (New Delhi : World Health Organization, Regional Office for South-East Asia, 1997)
Some presented at various international conferences, meetings, and seminars.
v. 1. Health imperatives for South-East Asia : 1994-1996 -- v. 2. Striving for better health in South-East Asia : 1997-2000.
Cover title.
Includes bibliographical references.
Keywords: Public health -- Southeast Asia